2015
DOI: 10.3389/fpls.2015.00124
|View full text |Cite
|
Sign up to set email alerts
|

Successional changes of phytodiversity on a short rotation coppice plantation in Oberschwaben, Germany

Abstract: To allow for information on successional changes in phytodiversity over time and space, as well as information on differences between clones and treatments, phytodiversity was monitored on a poplar short rotation coppice plantation in Oberschwaben, Southwest Germany, in four consecutive years. The investigated plantation was divided into two core areas, one planted with poplar clone Max4, the other with Monviso; each core area was divided into two blocks with alternating treatments: (i) irrigation and fertiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…This may explain the previously observed lack of differences between young and mature stands in hardwood forests [64], as the young stands under study were around 20 years old and recovery of forest plant species may already have been occurring, which seems to be confirmed by the fact that species composition was quite similar regardless of stand age. On the contrary, in another study of short rotation coppice plantations of poplar [23], the authors found that species richness decreased from the second year onwards. This pattern may be explained by the planting distance of 2.5 mˆ0.5 m, which should lead to much earlier canopy closure than in the present study or the previously mentioned study [20], in which the planting distances ranged from 5 mˆ5 m to 7 mˆ7 m.…”
Section: Comparison Of Different Types Of Poplar Plantationsmentioning
confidence: 83%
“…This may explain the previously observed lack of differences between young and mature stands in hardwood forests [64], as the young stands under study were around 20 years old and recovery of forest plant species may already have been occurring, which seems to be confirmed by the fact that species composition was quite similar regardless of stand age. On the contrary, in another study of short rotation coppice plantations of poplar [23], the authors found that species richness decreased from the second year onwards. This pattern may be explained by the planting distance of 2.5 mˆ0.5 m, which should lead to much earlier canopy closure than in the present study or the previously mentioned study [20], in which the planting distances ranged from 5 mˆ5 m to 7 mˆ7 m.…”
Section: Comparison Of Different Types Of Poplar Plantationsmentioning
confidence: 83%
“…Clapham and Slater [10] recorded 31 weed species within the miscanthus plantation, with Epilobium montanum, Ranunculus repens, and Rumex obtusifolius being the most frequently observed. Several studies [35][36][37], point to the fact that SRC species, as well as their varieties, influence the understory composition. We assume that this influence is due to different environmental conditions created by SRC crops.…”
Section: Discussionmentioning
confidence: 99%
“…(halophyte) and other herbaceous plants grown in tidal flat are dominant in the reclaimed land in South Korea [94], but other dominant plants might be formed in the understory vegetation formed after afforestation of the short rotation coppices, because of the shade effect [13]. Birmele et al [95] reported that the neighboring ground vegetation on SRC had a dominant tendency in light-demanding plant species. However, their proposition can be deteriorated from 62 to 39%, steadily over time, whereas the proposition of semi-shade species shows an increase from 22 to 34% as SRC trees change canopy levels.…”
Section: Successional Patterns In Flora On Srcmentioning
confidence: 99%
“…Monitoring the plant diversity in the area surrounding the SRC showed that the dominant species in the Saemangeum land reclamation area changed in their species composition over three years. Birmele et al [95] reported that high soil moisture and irrigated SRC plots might affect the high water ability of neighboring plants and impact species richness on successional changes in photodiversity of SRC, increasing the species number. In 2013, the dominant species in the SRC was identified to be S. viridis, but Sonchus brachyotus and C. epigeios also increased in 2014 (second rotation of the SRC).…”
Section: Successional Patterns In Flora On Srcmentioning
confidence: 99%